2021
DOI: 10.1097/tp.0000000000003890
|View full text |Cite
|
Sign up to set email alerts
|

HPi: A Novel Parameter to Predict Graft-related Outcome in Adult Living Donor Liver Transplant

Abstract: In accordance with the "DFG Guidelines on the Handling of Research Data," we will make all data available upon request. The data set will be archived for at least 3 y after the publication. This study was presented and was awarded the best oral article award at Liver Transplant Society of India (LTSI) conference held in December 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
1
8
2
Order By: Relevance
“…With so few SFSS events in the current study, we chose to use EAD as the endpoint of analysis. EAD has been reported to occur in 16% to 31% of LDLT series using mainly RLG (H5678) 5,12,15,46. Our EAD rate was 13.8% overall and 19.7% in LLG (H1234-MHV), which is still much lower than the previously reported rates of up to 50.8% in LLG (H1234-MHV) 5.…”
Section: Discussioncontrasting
confidence: 78%
“…With so few SFSS events in the current study, we chose to use EAD as the endpoint of analysis. EAD has been reported to occur in 16% to 31% of LDLT series using mainly RLG (H5678) 5,12,15,46. Our EAD rate was 13.8% overall and 19.7% in LLG (H1234-MHV), which is still much lower than the previously reported rates of up to 50.8% in LLG (H1234-MHV) 5.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous studies reported EAD occurred in 16% to 31% of LDLT series using mainly RLG, but it can be up to 50% in LLG. 10,12,42,43 Augmentation of venous outflow along with preplanned aggressive measures to lower excessive PV flow or pressure, such as pre or postreperfusion splenectomy, has allowed our program to have outstanding outcomes despite the high utilization of smaller LLG. 7 Interestingly, this study showed that the risk of EAD in LLG can be lowered by using a laparoscopic approach (21.1% for open and 10.4% for laparoscopic) with an OR of 0.36 (P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The hyperperfusion index of ≥ 9.97 mm Hg.cc/g predicted early graft outcomes and recipient mortality. [43] Besides portal hemodynamics, a non-mechanical impediment to free hepatic venous outflow from a high caval pressure may potentially jeopardize graft function. In a prospective observational study including 61 LDLT recipients, a post-LDLT high CVP of > 11 mm Hg led to functional HVO obstruction, thereby leading to elevated portal vein pressure by 45% and delayed recovery of graft function.…”
Section: Graft Hemodynamicsmentioning
confidence: 99%
“…[57] Table 3 summarizes the early predictive markers of EAD in LDLT. [43,48,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] Although the clinical use of these predictive biomarkers is not proven, we hypothesize that molecular biomarkers, combined with conventional clinical parameters, could lead to a more precise prediction of EAD after LDLT.…”
Section: Predictive Biomarkers Of Ead After Ldltmentioning
confidence: 99%
See 1 more Smart Citation